UPAYA NOVARTIS DALAM MEMPEROLEH HAK PATEN OBAT GLIVEC DI INDIA - Silvia Dhaniarti (2022)
The Glivec's patent case became one of the disputes regarding IPR ownership in India after TRIPS came into effect in 1995. It took 10 years for India to revise the Patent Law in its country to fully comply with TRIPS. The Novartis application case began to be reviewed in 2005 and in 2006 the Indian Patent Office issued a decision granting the patent for Glivec to Novartis. These results became the basis for Novartis to appeal to the Madras High Court, IPAB, and Supreme Court of India with writ two petitions, related to patent rejection and the Indian Patent Act, Section 3(D) which is considered to threaten the TRIPS agreement. Novartis has not only taken legal action to seek Glivec's patent in India but has also organized a global campaign and Glivec's free medical assistance program through GIPAP. This research is qualitative in nature using a descriptive method that takes the concepts of IPR and TRIPS in analyzing the problems that occur between Novartis and India related to the Glivec patent and explains how Novartis' efforts to obtain Glivec drug patents in India. The results of this study found that Novartis' efforts to obtain Glivec's patent rights in India did not change the decision of the Indian Patent Office. In addition, Novartis is very interested in the TRIPS agreement as the basis for filing patents in India as well as suing India. The definite suggestion in this study is to make a comparison between the TRIPS agreement and Indian Patent Law related to the standards of patent criteria applicable in India before applying patent for a new drug in India.